Pregnancy and polymorphisms in folate-cycle genes: what dose and formulation of folates to choose? - Н. А. Курмачёва; Е. В. Верижникова; О. М. Харитонова (Репродуктивная эндокринология, 2017)
Study objectives: To compare the course of pregnancy and perinatal outcomes of term delivery in women with polymorphisms in the folatecycle genes and a history of miscarriage, depending on what strategy was chosen to correct folate deficiency.